Cognitive Behavior Effects, Charismatic Attraction, Achievement of The Eligibility To The Convection of Sales Volume In The Moment of Choosing - Vina Merliana (Universitas Indonesia Membangun, 2024)
Sales volume is the number of units of the final result achieved by the company from the sale of products during a certain period. Sales are said to be an activity aimed at finding buyers and giving confidence to customers with the products offered, one of the factors that affect sales is the condition and ability of the seller, market conditions, capital, company organizational conditions and other factors. The research method used is descriptive and verification method, the data used is primary data with 71 respondents, the sampling technique uses purposive sampling method using the Slovin formula, the results of the t test (partial) x1 cognitive behaviors has no effect on sales volume, x2 charismatic appeal affects sales volume, x3 budget realization affects sales volume, while the f test (simultaneous) together there is an influence on sales volume.